Hypoglycemic potential of alcoholic root extract of Cassia occidentalis Linn. in streptozotocin induced diabetes in albino mice - Surbhi Sharma; Manjusha Choudhary; Sapna Bhardwaj; Nitesh Choudhary; Avatar Chand Rana (Faculty of Pharmacy, Cairo University, 2014)
Objective: Cassia occidentalis (CO) (family: Caesalpiniaceae) is a common weed which is widely used to treat inflammation, hepatotoxicity, antimalarial activities, sore eyes, hematuria, rheumatism, typhoid, asthma, leprosy and diabetes in folklore medicine in India. The present study was carried out to investigate the antidiabetic activity of ethanolic extract of C. occidentalis roots. Methods: Root extract of C. occidentalis (RCO) was administered orally at two doses (250 and 500 mg/kg) to normal and streptozotocin (STZ) induced NIDDM. Fasting blood glucose (FBG) level, biochemical parameters like blood glucose, serum cholesterol, high density lipoprotein (HDL) cholesterol, triglycerides (TG), total protein, urea, creatinine, serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) levels and physical parameters like change in body weight, food intake, water intake and levels in liver were performed for the evaluation of hypoglycemic effects. Results: Both the doses of RCO caused a marked decrease in FBG levels in STZ induced type 2 diabetic mice. RCO decreased the blood glucose, food intake, water intake, organ weight, serum cholesterol, TG, creatinine, SGOT and SGPT levels with significant value and increased the levels of HDL cholesterol and total protein with a significant value (P < 0.05-0.01). The decrease in body weight induced by STZ was restored with a significant value (P < 0.01) at both doses. Conclusion: The results suggest that ethanolic roots extract of C. occidentalis Linn. possesses hypoglycemic potential for the NIDDM and support the traditional use of the roots of plant as hypoglycemic agent.